Isolation of amylase producing bacteria from soil and identification by 16S rRNA gene sequencing and characterization of amylase - Islam, Tasnia (BRAC University, 2017)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2016.